International Handbook of Research in Professional and Practice-based Learning
XXI, 1383 p. 100 illus.
Keywords: The International Handbook of Research in Professional and Practice-based Learning discusses what constitutes professionalism, examines the concepts and practices of professional and practice-based learning, including associated research traditions and educational provisions. It also explores professional learning in institutions of higher and vocational education as well the practice settings where professionals work and learn, focusing on both initial and ongoing development and how that learning is assessed. The Handbook features research from expert contributors in education, studies of the professions, and accounts of research methodologies from a range of informing disciplines. It is organized in two parts. The first part sets out conceptions of professionalism at work, how professions, work and learning can be understood, and examines the kinds of institutional practices organized for developing occupational capacities. The second part focuses on procedural issues associated with learning for and through professional practice, and how assessment of professional capacities might progress. The key premise of this Handbook is that during both initial and ongoing professional development, individual learning processes are influenced and shaped through their professional environment and practices. Moreover, in turn, the practice and processes of learning through practice are shaped by their development, all of which are required to be understood through a range of research orientations, methods and findings. This Handbook will appeal to academics working in fields of professional practice, including those who are concerned about developing these capacities in their students. In addition, students and research students will also find this Handbook a key reference resource to the field.